Dampak Ekonomi Pola Konsumsi Energi dan Jejak Karbon Pekerja Sektor Informal di Perkotaan - Primajana, Dewa Jati; Premananda, Wayan Hari (Bumi Lestari, 2025)
The informal sector, which includes small and micro businesses, plays a significant role in urban economies but often faces challenges in terms of energy efficiency and sustainability. Despite its important contribution to the local economy, inefficient energy consumption can lead to increased operational costs and negative environmental impacts, such as greenhouse gas emissions and air pollution. This study uses both qualitative and quantitative approaches to identify energy consumption patterns in the informal sector and evaluate the economic and environmental impacts of these practices. The findings indicate that low awareness of energy efficiency and limited access to environmentally friendly technologies result in high energy consumption and significant negative impacts, both economically and environmentally. The adoption of more efficient and sustainable energy solutions can reduce energy costs, improve worker welfare, and reduce negative environmental impacts. Therefore, this study suggests the importance of policies that support the development of a more sustainable informal sector, with a focus on improving energy efficiency and reducing environmental impacts.